RED BLOOD CELL COUNT, HEMOGLOBIN LEVEL, AND THE HEMATOCRIT OF LANDRACE SWINE WERE GIVEN FEED WATER HYACINTH FROM LEAD POL - Putri, Putu Vindhy Chempaka; Budaarsa, Komang; Dharmawan, Nyoman Sadra (Buletin Veteriner Udayana, 2017)
The experimental study was done using a completely randomized design, and the aim of this study is to determine the effect of water hyacinth ( Eichhornia crassipes ) collected from polluted water in feed on the red blood cell ( RBC) count, hemoglobin level , and the hematocrit . A total of eight Landrace pigs were used in this study, consisted of four groups: pigs were fed without hyacinth (A), pigs were fed with 2.5% hyacinth (B), pigs were fed with 5.0% hyacinth (C), and pigs were fed with 7.5% hyacinth (D). Blood were then collected from auricularis superficialis vein. RBC count, hemoglobin level , and the hematocrit ??were measured using routine hematological examination by auto analyzer machine Scil Vet ABC (ABC Vet 16p) . Data were then analyzed by one-way ANOVA . The results showed that the administration of water hyacinth ( Eichhornia crassipes ) collected from Lead (Pb) polluted water was not influence the RBC count, hemoglobin level, and the hematocrit in pig (p>0.05).
Keywords: babi Landrace; eceng gondok; timbal (Pb); total eritrosit; kadar hemoglobin; nilai hematokrit